R. T. Ridley. History of Rome, A Documented Analysis (Problemi e ricerche di storia antica. 8). Roma, «L’Erma” di Bretschneider. 1987. 696 Pp. + 15 itoj. - Martínez-pinna, Jorge (Gerión. Revista de Historia Antigua, 1990)
Sin resumen